Design and Evaluation of Performance for Text and Image Cryptography Using Biometric Key and ECC - Kukreja, Anu; Ayushi, (International Journal of Computer Sciences and Engineering, 2014)
Cryptography is one of the important sciences in the current era. It is a science of secret writing. It is the art of protecting the information by transforming it into an unreadable format in which a message can be concealed from the casual reader and only the intended recipient will be able to convert it into original text .Cryptography renders the message unintelligible to outsider by various transformations. Data Cryptography is the scrambling of the content of data like text, image, audio and video to make it unreadable or unintelligible during transmission. Its main goal is to keep the data secure from unauthorized access. The importance of cryptography comes from the intensive digital transactions which we daily perform on the internet and other communication channels. Visual cryptography, an emerging cryptography technology, uses the characteristics of human vision to decrypt encrypted images. It needs neither cryptography knowledge nor complex computation. For security concerns, it also ensures that hackers cannot perceive any clues about a secret image from individual cover images. In this work, the authentication of the user will be verified based on the user information as well as the signature. It means the cryptography will be performed over the text information as well as on digital signature. This two layer scheme will improve the security for the authentication. The proposed algorithm is implemented on both text and image for encoding and decoding purpose. All the implementation work has been done in MATLAB R2009 using general MATLAB toolbox and image processing toolbox. Encryption time, decryption time and size of encrypted data have been taken as parameter for evaluation of performance of algorithm.